Potensi Jarak Pagar (Jatropha curcas) sebagai Larvasida Hayati Pencegah Penyakit Demam Berdarah Dengue - Dyah Iswantini; Adi Riyadhi; Upik Kesumawati; Rosihan Rosman; Djumali Mangunwidjaja; Min Rahminiwati (Jurnal Ilmu Pertanian Indonesia, 2011)
Recently, Indonesia has big problem caused by dengue haemorraghic fever with A. aegypti as vector. Potential medicine and vaccine for curing this disease have not been found. The effective method to prevent this disease is the use of A. aegypti larvicidal. The chemical larvicidal has disadvantage for evironmental aspect. To solve this problem, the biological larvicidal has a good chance to develop. Indonesia has megadiversity which can be developed as biological larvicidal. Crude aqueous extracts and ethanol extracts of Jatropha curcas (Jarak pagar) seed and oil of Jatropha curcas were evaluated for larvicidal potential against the Aedes aegypti mosquito. Among all extracts, Jatropha curcas oil possessed a highest activity against the 3th instar larvae of Aedes. LC50 values of Jatropha curcas oil was 1507 ppm for 24 h and 866 ppm for 48 h. It was suggested that the Croton tiglium oil and Jatropha curcas oil possess larvicidal properties that could be developed and used as biological larvicidal.